Feasibility of Water Injection on the Coal Wall of Loose Thick Coal Seam to Prevent Rib Spalling and Its Optimal Moisture Content - Jian Sun; Bin Li; Ruofei Zhang; Zhou Huang (Geofluids)
Rib spalling of loose thick coal wall seriously restricts the high yield, high efficiency of coal mine, affecting the safety production of coal mine. Based on the engineering background of water injection to control rib spalling of loose thick coal seam in the Luling Coal Mine of the Huaibei Mining Group, the mineral composition and microscopic morphology of III811 loose thick coal seam in Luling Coal Mine were analyzed by X-ray diffraction and scanning electron microscope. Through uniaxial compressive strength tests of coal samples with different moisture content, the relationship between uniaxial compressive strength, peak strain and moisture content, and their failure characteristics was studied. The results showed that the natural moisture content of III811 coal seam in Luling coal mine is low, and it contains a large amount of kaolinite (75.2%) belonging to clay mineral which is easy to absorb water and then expand, fully bond loose coal body and fill cracks to improve the integrity of coal body. These two factors provide feasibility for injecting water in workface to prevent rib spalling. The compressive strength of coal samples decreased slowly with the raise of moisture content, while the peak strain increased first and then decreased. The peak strain was the largest when the water content was 6.0%. The failure degree of coal samples intensifies with the increase of water content, and the failure form changes from tensile failure at low water content to shear failure at high water content. Considering the relationship between compressive strength, peak strain, and moisture content of coal samples, the optimal moisture content of III811 workface in loose thick coal seam is determined to be 4.5% ~6%.